Racial inequality in the production of fresh vegetables and cut flowers in Argentina: an analysis in Greater La Plata - Nuria Caimmi (Salud Colectiva)
This study aims to analyze the configuration of inequalities in one of Argentina’s most significant production zones for fresh vegetables and cut flowers, located in Greater La Plata, Buenos Aires Province. This ongoing anthropological research, initiated in 2021, employs methods such as participant observation, interviews, food mapping, and digital ethnography. Among the main findings, we highlight that this production zone exhibits, in both its origins and daily operations, certain racist dynamics that are not solely generated by the host society toward migrants but are disseminated throughout the social fabric, including by migrant producers themselves. Positive valuations of ultra-processed foods by those living and working in the area reflect the importance of belonging to the host society, running parallel to strategies for preserving food preparations from before migration. These include the recreation of a “food identity” and the proliferation of “legumbrerías” (legume shops) and “paisano eateries” (restaurants serving traditional food). These transformations are intertwined with the productive changes migrants have experienced, shifting from peasant economies in their places of origin to intensive production in Greater La Plata.